2016
DOI: 10.1248/cpb.c16-00114
|View full text |Cite
|
Sign up to set email alerts
|

The Safety and Immunological Effects of rAd5-EBV-LMP2 Vaccine in Nasopharyngeal Carcinoma Patients: A Phase I Clinical Trial and Two-Year Follow-Up

Abstract: Epstein-Barr virus (EBV)-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 25 publications
0
27
0
Order By: Relevance
“…The completed Phase 1 (NCT01147991, Table 1 ) trial showed safety, with only grade I/II adverse events. An immune response with increased circulating CD4 + T cells and antigen-specific T cell responses was reported [ 82 , 83 ]. A separate MVA-based vaccine study targeting EBNA1 and LMP2 led to increased CD4 + and CD8 + T-cell responses to at least one vaccine antigen in 15 of 18 patients [ 97 ].…”
Section: Virus-derived Tumour Antigensmentioning
confidence: 99%
See 1 more Smart Citation
“…The completed Phase 1 (NCT01147991, Table 1 ) trial showed safety, with only grade I/II adverse events. An immune response with increased circulating CD4 + T cells and antigen-specific T cell responses was reported [ 82 , 83 ]. A separate MVA-based vaccine study targeting EBNA1 and LMP2 led to increased CD4 + and CD8 + T-cell responses to at least one vaccine antigen in 15 of 18 patients [ 97 ].…”
Section: Virus-derived Tumour Antigensmentioning
confidence: 99%
“…Similarly, a recombinant Ad5-EBV-LMP2 vaccine was tested in NPC patients in a Phase 1 clinical trial and was well tolerated (NCT00078494, Table 1 ). Higher proportions of CD4 + T cells were detected in the high dosage group; however, no other functional tests have been done [ 82 ].…”
Section: Virus-derived Tumour Antigensmentioning
confidence: 99%
“…1). 185,[220][221][222] Finally, a few studies preferred to use "unpulsed" autologous (matured ex vivo) DCs, administered in combination with cytokineinduced killer cells (CIKs), chemotherapy and/or radiotherapy. [223][224][225][226] Other approaches included the use of autologous dendritomas, 227 allogeneic peripheral blood mononuclear cells matured ex vivo into DCs, 228,229 or autologous unpulsed DCs combined with ACT.…”
Section: Completed Clinical Trialsmentioning
confidence: 99%
“…5,6 In the last decade, cancer immunotherapy has emerged as a clinically effective tool in several solid tumors, particularly in combination with more conventional therapies. 7 There are a variety of approaches in tumor immunotherapy, including manipulation of the immune system through the use of immune agents, such as vaccines, 8 cytokines, 9 checkpoint inhibitors (including anti-programmed death 1 [PD-1]/PD-ligand 1 [PD-L1] antibodies and anti-cytotoxic T-lymphocyte-associated antigen (CTLA)-4 antibodies 10,11 ), kinase inhibitors (such as apatinib and gefitinib), 12,13 and immune cells. [14][15][16][17][18][19][20] Among all the possible strategies, cellular immunotherapy has flourished and is widely used in tumor treatment, especially in Asia.…”
Section: Introductionmentioning
confidence: 99%